2004
DOI: 10.1007/s00213-004-1938-z
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of human COMT alleles in brain and lymphoblasts detected by RT-coupled 5? nuclease assay

Abstract: COMT alleles are differentially expressed. The Met158 allele predicts higher mRNA expression in both brain and lymphoblasts. As exemplified here, the RT-coupled 5' nuclease assay is a reliable method for the quantitative evaluation of cis-acting regulatory effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 29 publications
(37 reference statements)
3
41
0
2
Order By: Relevance
“…The Val158 allele is approximately three times more thermostable than Met158 at normal body temperature, and has 40% higher activity 72 . Furthermore, Val158 and Met158 are found on differentially expressed haplotype backgrounds 73 of ancient origin, as indicated by their opposite (yin-yang) allelic configurations (a 5-locus haplotype pattern of 1122Val versus 2211Met) that are both abundant in populations worldwide 74 . The haplotype analyses predict variation in COMT expression, and it is likely that COMT linkage studies will incorporate haplotype information to capture more details on the functional genetic variation of this gene.…”
Section: Genes and Neurobiologiesmentioning
confidence: 99%
“…The Val158 allele is approximately three times more thermostable than Met158 at normal body temperature, and has 40% higher activity 72 . Furthermore, Val158 and Met158 are found on differentially expressed haplotype backgrounds 73 of ancient origin, as indicated by their opposite (yin-yang) allelic configurations (a 5-locus haplotype pattern of 1122Val versus 2211Met) that are both abundant in populations worldwide 74 . The haplotype analyses predict variation in COMT expression, and it is likely that COMT linkage studies will incorporate haplotype information to capture more details on the functional genetic variation of this gene.…”
Section: Genes and Neurobiologiesmentioning
confidence: 99%
“…Recently, the low activity Met allele has been reported as a risk factor for cognitive decline in 22q11DS. 43 Most work to date has focussed on the Val/Met polymorphism and other variants reported to be associated with altered mRNA expression 44,45 have not been widely studied. However, on the current evidence, the mechanism for the cognitive effects at COMT is unlikely to be simple.…”
Section: Association Studies Of Comt and Frontal Lobe Functionmentioning
confidence: 99%
“…This suggestion is broadly compatible with the demonstration of cis-acting loci that modify the expression of COMT mRNA independent of the Val/ Met locus. 44,45 However, there are also data that argue strongly against the existence of more than one even moderately common functionally relevant polymorphism in COMT. Thus, while Chen et al 10 demonstrated that brain COMT enzyme activity is associated with the Val/Met locus, this did not correlate with the markers that we and others have associated with mRNA expression 44,45 or with schizophrenia.…”
Section: Schizophreniamentioning
confidence: 99%
“…The valine allele (472G) has initially been reported to result in a three-to fourfold higher COMT activity as compared to the methionine allele (472A) (Lachman et al, 1996). However, the valine allele appears to be less expressed in the brain as compared to the methionine allele (Bray et al, 2003;Zhu et al, 2004), which slightly mitigates the effect to about 40% increased enzyme activity as conferred by the valine allele (Chen et al, 2004). The COMT val158met polymorphism has repeatedly been investigated for association with major depression with contradictory reports of no association (Kunugi et al, 1997;Frisch et al, 1999;Cusin et al, 2002;Serretti et al, 2003), possible association with the valine allele (Massat et al, 2005;Funke et al, 2005) or conversely the methionine allele (Ohara et al, 1998).…”
Section: Introductionmentioning
confidence: 99%